Aerodynamics of cyclist posture, bicycle and helmet characteristics in time trial stage - Chabroux, V.; Barelle, C.; Favier, D. (Journal of Applied Biomechanics, 2012)
The present work is focused on the aerodynamic study of different parameters, including both the posture of a cyclist`s upper limbs and the saddle position, in time trial (TT) stages. The aerodynamic influence of a TT helmet large visor is also quantified as a function of the helmet inclination. Experiments conducted in a wind tunnel on nine professional cyclists provided drag force and frontal area measurements to determine the drag force coefficient. Data statistical analysis clearly shows that the hands positioning on shifters and the elbows joined together are significantly reducing the cyclist drag force. Concerning the saddle position, the drag force is shown to be significantly increased (about 3%) when the saddle is raised. The usual helmet inclination appears to be the inclination value minimizing the drag force. Moreover, the addition of a large visor on the helmet is shown to provide a drag coefficient reduction as a function of the helmet inclination. Present results indicate that variations in the TT cyclist posture, the saddle position and the helmet visor can produce a significant gain in time (up to 2.2%) during stages.